2011
DOI: 10.1016/j.jcp.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Finite volume schemes for dispersive wave propagation and runup

Abstract: Finite volume schemes are commonly used to construct approximate solutions to conservation laws. In this study we extend the framework of the finite volume methods to dispersive water wave models, in particular to Boussinesq type systems. We focus mainly on the application of the method to bidirectional nonlinear, dispersive wave propagation in one space dimension. Special emphasis is given to important nonlinear phenomena such as solitary waves interactions, dispersive shock wave formation and the runup of br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 70 publications
0
93
1
Order By: Relevance
“…A large number of numerical methods have been developed in the past few years for the BT equations. Let us mention for instance some Finite-Difference (FDM in the following) approaches [49,54,65,75], Finite-Element methods (FEM in the following) [46,59,66,73], Finite-Volume discretizations (FVM in the following) for 1d equations [21], hybrid FDM / FVM [24,25,55,64,69], or even a purely 2d FVM discretization on unstructured recently been performed in [43]. Let us also mention [10] and more recently [63] for a 2D cartesian numerical model based on fully non-linear BT equations of [76].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of numerical methods have been developed in the past few years for the BT equations. Let us mention for instance some Finite-Difference (FDM in the following) approaches [49,54,65,75], Finite-Element methods (FEM in the following) [46,59,66,73], Finite-Volume discretizations (FVM in the following) for 1d equations [21], hybrid FDM / FVM [24,25,55,64,69], or even a purely 2d FVM discretization on unstructured recently been performed in [43]. Let us also mention [10] and more recently [63] for a 2D cartesian numerical model based on fully non-linear BT equations of [76].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical scheme presented above has already been validated in several studies even in the case of dispersive waves [24,25]. Consequently, we do not present here the standard convergence tests which can be found in references cited above.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This goal is achieved by various so-called reconstruction procedures, such as MUSCL TVD [38,59], UNO [35], ENO [34], WENO [64] and many others. In our previous study on Boussinesq-type equations [24], the UNO2 scheme showed a good performance with low dissipation in realistic propagation and runup simulations. Consequently, we retain this scheme for the discretization of the modified Saint-Venant equations.…”
Section: High-order Reconstructionmentioning
confidence: 88%
See 1 more Smart Citation
“…The extension to more realistic bi-directional wave propagation models such as Boussinesq type equations [40,36,32,16].…”
Section: Discussionmentioning
confidence: 99%